Study on the rainfall change in Pisha stone area. Issue 2 (September 2019) - Shen, Zhenzhou; Yao, Wenyi; Xiao, Peiqing; Li, Mian; Yang, Jishan; Jing, Chengran; Zhang, Pan; Wang, Zhihui; Liu, Hui
Abstract: Rainfall and raindrop characteristics have an important impact on the erosion of sandstone soil. The LPM laser raindrop spectrometer is used to analyze the rainfall characteristics of the Ordos City in the Yellow River Basin, including the distribution characteristics of the velocity and size of a natural rainfall raindrop. Statistical analysis shows that with the gradual strengthening of rainfall intensity, the number of raindrops per unit time, the size and speed of raindrops will increase parabolically. However, the natural rainfall process finds that the diameter and velocity of the raindrop are relatively scattered. During this measurement, the velocity of raindrops is mainly distributed between 1-3.4m / s, and most raindrops are distributed at 1-1.8m / s. The diameter of the raindrops is mainly distributed in the range of 0.125-0.5 mm. The raindrops with a diameter of 0.125mm are mainly distributed between 0.8-3.4m / s, the raindrops with a diameter of 0.25mm are mainly distributed between 1-2.6m / s, and the raindrops with a diameter of 0.375mm are mainly distributed between 1.0-2.2 m/s, and the diameter of 0.5 mm is mainly distributed in the range of 2.2-2.6 m / s.